Peak running intensity of elite female field hockey players during competitive match play - McGuinness, A.; Passmore, D.; Malone, S.; Collins, K. (The Journal of Strength and Conditioning Research, 2022)
In recent years, backroom coaching staff have relied heavily on the global demands of competitive match-play to monitor running performance within training and match environments. Although, these figures help prepare players for the demands of match-play, they do not account for the physical and physiological stress of the most intense periods of competition. The aim of the current study was to quantify the duration and position-specific maximal running performance during match-play using a 1-10-minute moving average epoch methodology. Twenty-six (n = 26) elite international female field hockey players (23 ± 3 years; 162.6 ± 13 cm; 66 ± 6 kg) participated in the current observational study. Data were collected during 22 international games, resulting in over 360 individual samples (n = 368) being obtained for analysis. Players were categorized based on their positional lines of play (defenders, midfielders, and forwards). Variables of interest included relative total (m·min-1), high-speed (>16 km·h-1; m·min-1) and sprint distance (>20 km·h-1; m·min-1). Regardless of position, varying differences were observed between 10-minute rolling average for relative total (mod—large), high-speed (mod-large), and sprint (mod—large) distance respectively. Furthermore, as the duration of the rolling average increased, so did the observed differences (small). The forwards (119.3 ± 19.7 m·min-1) were reported to have the highest peak output during minute one for relative high-speed distance when compared with the defenders (100.7 ± 19.7, effect size [ES] 0.9, large) and the midfield (106.8 ± 23.4 m·min-1, ES 0.5, moderate). The results of the current study show that the running performance of field hockey players alters during match-play irrespective of moving average. Finally, the data will aid practitioners in the development of sport-specific drills to adequately prepare hockey players for the maximal intensity periods of elite hockey match-play.